Library System for Elementary Education:Fourth Plan Period - Hithaishini, M. V. (Journal of Information and Knowledge, 2000)
This paper is based on the data for 1960-61, which are the latest available. Using the rate of increase in 1960-61, the elementary school enrolment, including: enrolment in the elementary department of high schools during the Fourth Plan. Period, is calculated. On the basis of a library fund of one rupee perpupil, the. annual library fund for the Elementary School Library System in. India is of the order of Rs 74 million in 1966-67 and of Rs 108 million in 1970-71.